Clustered distribution of virus infected cells in the liver of patients with chronic hepatitis C - Falcón, Viviana; Acosta-Rivero, Nelson; González, Sirenia; Acosta Medina, Emilio; Garateix Suárez, Rocio; Silva, José A.; Ãlvarez-Lajonchere, Liz; MartÃnez-Donato, Gillian; Rosales, Carmen M.; Dueñas-Carrera, Santiago; et al. (Revista Cubana de Medicina Tropical, 2017)
Introduction: detection of hepatitis C virus RNA and proteins in the liver can not only contribute to the knowledge of the mechanisms of HCV replication and pathogenesis but also complement diagnostics and therapeutic studies. Objective: to determine the presence of hepatitis C virus in the liver of patients with chronic hepatitis C that were immunized with a therapeutic vaccine candidate. Methods: detection of hepatitis C virus RNA and proteins were studied by in situ hybridization and immunofluorescence assays in liver biopsies from 14 hepatitis C virus -infected individuals. Results: hybridization signals for hepatitis C virus-RNA of both positive and negative polarity were detected in the cytoplasm of hepatocytes from most of the samples analyzed. However, the HCV structural antigens could not be detected in any of the samples. The hepatitis C virus RNA was observed on granular structures in the cytoplasm of hepatocytes. This staining pattern is similar to that described for stress granules and/or lipid droplets which are involved in hepatitis C virus replication. The proportion of cells showing positive reactions for hepatitis C virus RNA of negative polarity (which is a marker of ongoing viral replication) ranged from 4.47 % to 15.94 %. Conclusions: results from this work suggest that hepatitis C virus infection occurs in groups of neighbouring hepatocytes that are distributed sporadically in the liver. This is consistent with the model of clustered spatial distribution of hepatitis C virus infected cells and cell to-cell spread of hepatitis C virus in the liver, and suggests that hepatitis C virus replication was constrained in these patients.